First Egg and Standardized Nest Description of the Southern Bristle-Tyrant (Phylloscartes eximius) - Tonetti, Vinicius Rodrigues [UNESP]; Gussoni, Carlos O.A. [UNESP]; Pizo, Marco A. [UNESP] (Taylor & Francis, 2017)
In spite of its relevance, data on nest architecture and egg morphology are lacking for several bird species, especially in the Neotropics. We provide the first egg and standardized nest description of the Southern Bristle-Tyrant (Phylloscartes eximius), a species considered in the genus Pogonotriccus by some authors. Similarly to two other studies, the nest was a closed/globular/lateral structure built mostly with moss and spider web. The only egg we found was clean white and measured 17.1 mm length x 13.5 mm width. Given the plasticity of nest building and the low sample size, more nests should be described to infer relatedness among Phylloscartes and Pogonotriccus using nest architecture. Similarly, more eggs of these species should be described.
Keywords: Atlantic Forest; breeding biology; phylogenetic relationship; Pipromorphinae; Pogonotriccus; Rhynchocyclidae; Serra da Cantareira